2023
DOI: 10.1186/s12929-023-00902-w
|View full text |Cite
|
Sign up to set email alerts
|

Marine prebiotics mediate decolonization of Pseudomonas aeruginosa from gut by inhibiting secreted virulence factor interactions with mucins and enriching Bacteroides population

Abstract: Background Pseudomonas aeruginosa intestinal carriage rates are significantly higher in immunosuppressed individuals and hospitalized patients who therefore have increased risk of infections and antibiotic-associated diarrhea. To combat intestinal dysbiosis and decolonize P. aeruginosa from gastrointestinal tract, we investigated the anti-adherence and gut microbiota modulation properties of marine prebiotic fucoidans. Methods Proteomic analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Pseudomonas, although a common opportunistic pathogen, is not readily able to infect the gut (Chuang et al 2017). Species such as Pseudomonas aeruginosa are more often associated with lung infections and with enterocolitis in children (Hoff et al 2020;Janapatla et al 2023). Bamboo shoots, while nutrient rich and protein dense, may initiate an increase in pathogenic microorganisms due to their high and undigested protein content, potentially elevating the risk of metabolic diseases (Zhao et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas, although a common opportunistic pathogen, is not readily able to infect the gut (Chuang et al 2017). Species such as Pseudomonas aeruginosa are more often associated with lung infections and with enterocolitis in children (Hoff et al 2020;Janapatla et al 2023). Bamboo shoots, while nutrient rich and protein dense, may initiate an increase in pathogenic microorganisms due to their high and undigested protein content, potentially elevating the risk of metabolic diseases (Zhao et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…2020; Janapatla et al. 2023). Bamboo shoots, while nutrient rich and protein dense, may initiate an increase in pathogenic microorganisms due to their high and undigested protein content, potentially elevating the risk of metabolic diseases (Zhao et al.…”
Section: Discussionmentioning
confidence: 99%
“…The normalized intensity was recorded and fitted to equation 2 for determination of the IC50 value (AAT Frye 12 Bioquest, equation adapted in Origin Pro) for the experiment. (48)(49)(50)(51)(52) In equation 2, F max and F min represent the maximum and minimum fluorescent intensities of the experiment. F o represents the fluorescent intensity at each data point, and [S] o represents the concentration of competing ligand, in this case the FANAs or untagged miRs.…”
Section: Steady-state Fluorescence Spectroscopymentioning
confidence: 99%
“…There have been successful examples of using probiotics and FMT to treat its infection in humans [163,164]. Janapatla et al reported that a kind of prebiotic extracted from marine plants, fucoidans, is helpful in clearing P. aeruginosa from the GI tract of mice by inhibiting the release of some virulence factors and promoting the growth of Bacteroides, whose growth could be suppressed using antibiotic treatment [165].…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%